2007
DOI: 10.1111/j.1744-6570.2007.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recent Developments in Integrity Test Research

Abstract: A sizable body of new literature on integrity tests has appeared since the last review of this literature by Sackett and Wanek (1996). Understanding of the constructs underlying integrity tests continues to grow, aided by new work at the item level. Validation work against a growing variety of criteria continues to be carried out. Work on documenting fakability and coachability continues, as do efforts to increase resistance to faking. New test types continue to be developed. Examination of subgroup difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(65 citation statements)
references
References 72 publications
2
60
2
1
Order By: Relevance
“…However, even in the case of predicting broad and complex behaviours, narrow traits have been found to explain more variance than broad traits, suggesting that, overall, narrow traits have higher predictive 1 Note that these studies assessed overt Integrity, which differs from Honesty-Humility; overt integrity tests are not personality-based and are mostly developed to assess the predisposition of job applicants to exhibit counterproductive behaviour (e.g. Berry, Sackett, & Wiemann, 2007). Despite the different operationalization of overt Integrity and HonestyHumility, several studies have provided evidence that Honesty-Humility is strongly associated with overt Integrity (Lee, Ashton, & De Vries, 2005;Marcus et al, 2007).…”
Section: Narrow Personality Traits and Academic Criteriamentioning
confidence: 99%
“…However, even in the case of predicting broad and complex behaviours, narrow traits have been found to explain more variance than broad traits, suggesting that, overall, narrow traits have higher predictive 1 Note that these studies assessed overt Integrity, which differs from Honesty-Humility; overt integrity tests are not personality-based and are mostly developed to assess the predisposition of job applicants to exhibit counterproductive behaviour (e.g. Berry, Sackett, & Wiemann, 2007). Despite the different operationalization of overt Integrity and HonestyHumility, several studies have provided evidence that Honesty-Humility is strongly associated with overt Integrity (Lee, Ashton, & De Vries, 2005;Marcus et al, 2007).…”
Section: Narrow Personality Traits and Academic Criteriamentioning
confidence: 99%
“…According to this view, a deviated moral compass is evidence of an individual"s faulty human nature. Indeed, the idea that psychometric tests can identify "bad apples" before they are hired underlies the common practice of integrity testing among employers (Berry, Sackett, & Wiemann, 2007;Van Iddekinge, Roth, Raymark, & OdleDusseau, 2012).…”
Section: The Moral Compassmentioning
confidence: 99%
“…Previous research has shown that both overt and personality-based integrity tests predict job performance, training performance, and counterproductive behaviors, including absenteeism and theft (e.g., Berry, Sackett, and Tobares, 2010;Berry, Sackett, and Wiemann, 2007;Cullen and Sackett, 2004;Ones, Viswesvaran, and Schmidt, 1993;Van Iddekinge et al, 2012). Integrity tests can also predict drug and alcohol abuse (Schmidt, Viswesvaran, and Ones, 1997).…”
Section: Criterion-related Validity For Integrity Testsmentioning
confidence: 99%
“…Situational characteristics, such as alienation and negative peer-group exposure, were also associated with scores on the two test types and were more strongly related to test scores than were individual characteristics-leading to questions about whether integrity tests identify enduring individual characteristics, which is their intent, or more-malleable situational characteristics. A later review of the association between integrity tests and situational and individual characteristics concluded that both situational and individual characteristics influence scores, and researchers should perhaps consider the interaction between individual characteristics and social context to better understand scores (Berry, Sackett, and Wiemann, 2007).…”
Section: Associations Among Measuresmentioning
confidence: 99%